Efectos de la estimulación transcraneal con corriente directa anódica y catódica sobre la corteza prefrontal en la reconsolidación y extinción de memorias de miedo en ratas (2020)
Despite the therapeutically advantage that represent the reconsolidation for pathological memories underpinning a wide range of neuropsychiatric diseases, most of the pharmacological agents interfering with the reconsolidation are not approved for human testing. Additionally, extinction provides an effective and practical, but not permanent, method of addressing pathogenic emotional responses. Transcranial direct current stimulation (tDCS) is a non-invasive neurostimulation technique used to alter cortical neuronal excitability via externally applied electric fields. However, there is a lack of evidence about the effect of these technology to modify memory traces via reactivation/reconsolidation mechanism. In this study, we evaluate the effect of cathodal and anodal transcranial direct current stimulation applied after memory reactivation and extinction in rats...